A speckle-imaging search for close triple companions of cataclysmic binaries. Issue 1 (5th August 2021) - Shara, Michael M; Howell, Steve B; Furlan, Elise; Gnilka, Crystal L; Moffat, Anthony F J; Scott, Nicholas J; Zurek, David
ABSTRACT: The orbital periods of most eclipsing cataclysmic binaries are not undergoing linear secular decreases of order a few parts per billion as expected from simple theory. Instead, they show several parts per million increases and decreases on time-scales of years to decades, ascribed to magnetic effects in their donors, triple companions, or both. To directly test the triple companion hypothesis, we carried out a speckle-imaging survey of six of the nearest and brightest cataclysmic variables. We found no main-sequence companions earlier than spectral types M4V in the separation range ∼0.02–1.2 arcsec, corresponding to projected linear separations of ∼2–100 au, and periods of ∼3–1000 yr. We conclude that main-sequence triple companions to cataclysmic variables are not very common, but cannot rule out the presence of the faintest M dwarfs or close brown dwarf companions.